Utility of MF-non coding region for measles molecular surveillance during post-elimination phase, Spain, 2017–2020 - Jacqueline, Camille; Gavilán, Ana María; López-Perea, Noemí; Penedos, Ana Raquel; Masa-Calles, Josefa; Echevarría, Juan E.; Fernández-García, Aurora; , on behalf of the MMR Study Group (Frontiers in Microbiology, 2023)
In countries entering the post-elimination phase for measles, the study of variants by sequencing of 450 nucleotides of N gene (N450) does not always allow the tracing of chains of transmission. Indeed, between 2017 and 2020, most measles virus sequences belonged to either the MVs/Dublin.IRL/8.16 (B3-Dublin) or the MVs/Gir Somnath.IND/42.16 (D8-Gir Somnath) variants. We evaluated the additional use of a non-coding region (MF-NCR) as a tool to enhance resolution and infer case origin, chains of transmission and characterize outbreaks. We obtained 115 high-quality MF-NCR sequences from strains collected from Spanish patients infected with either B3-Dublin or D8-Gir Somnath variants between 2017 and 2020, performed epidemiological, phylogenetic and phylodynamic analyses and applied a mathematical model to determine relatedness among identified clades. Applying this model allowed us to identify phylogenetic clades potentially derived from concomitant importations of the virus rather by a single chain of transmission, inferred based on only N450 and epidemiology data.. In a third outbreak, we found two related clades that corresponded to two chains of transmission. Our results show the ability of the proposed method to improve identification of simultaneous importations in the same region which could trigger enhanced contact tracing. Moreover, the identification of further transmission chains indicates that the size of import-related outbreaks was smaller than previously found, supporting the interpretation that endemic measles transmission was absent in Spain between 2017 and 2020. We suggest considering the use of the MF-NCR region in conjunction with the study of N450 variants in future WHO recommendations for measles surveillance.